Effect of adhesive strategy on resin cement bonding to dentin. Issue 3 (25th October 2022) - Mazzitelli, Claudia; Maravic, Tatjana; Josic, Uros; Mancuso, Edoardo; Generali, Luigi; Checchi, Vittorio; Breschi, Lorenzo; Mazzoni, Annalisa
Abstract: Objective: The cement bonding strategy and the polymerization mode can influence the prognosis of indirect restorations. The microtensile bond strength (μTBS) and dentin endogenous enzymatic activity of a dual‐cure resin cement (PV5) used in combination with two dentin surface conditioners (accelerator‐enhancer primer, TP or universal adhesive, UA) were evaluated. Materials and Methods: PV5 was used to lute composite overlays after dentin treatment with TP or UA. The resin cement was self‐cured, SC (1 h at 37 °C) or dual‐cured, DC (20 s light‐cure followed by 15 min self‐cure at 37°C). The μTBS test, fractographic analysis, and the in situ zymography evaluations were performed after 24 h ( T 0 ) or 1 yr ( T 12 ) of artificial storage. Data were statistically analyzed (α = 0.05). Results: TP/DC obtained the highest adhesive strengths (45 ± 9 and 36.6 ± 8), while UA/SC (17 ± 8 and 11 ± 4) the lowest, both at T 0 and T 12, respectively. DC resulted in superior bonding values than the SC, independent of the dentin surface treatment ( p < 0.05). The type of adhesive, curing mode and aging influenced the gelatinolytic activity ( p < 0.05). Conclusions: The dual‐cure resin cement used in combination with its accelerator‐enhancer primer showed superior bonding performances with respect to universal adhesive. Dual‐curing the resin cement was determinant to enhance bonding capability over time, independent of the adhesive strategy. Clinical Relevance: Clinicians must be aware to faithfully follow manufacturer's recommendation regarding the adhesive strategy suggested with the resin cement used.